Unveiling the Key Influencers in Smartphone Purchase Decisions - Rana, Nabin Kumar (Devkota Journal of Interdisciplinary Studies, 2023)
In this study, the objective was to delve deep into the determinants that sway consumer’s smartphone purchasing choices in Butwal, Sub-Metropolitan City. Analyzing the role of societal influences, intrinsic product characteristics, and the perceived brand reputation, the study delineates the fundamental considerations guiding consumers in the selection of smartphones. In the rapidly expanding smartphone market of Butwal, Sub-Metropolitan City, understanding the consumer’s criteria for smartphone selection and the most prominent influencer in their decisions is of utmost importance. The research relied heavily on primary data, garnered from 385 smartphone users within Butwal, Sub-Metropolitan City, through a meticulously crafted questionnaire, leveraging a convenience sampling strategy. To pinpoint the critical factors affecting customer’s smartphone buying tendencies, a combination of descriptive analysis, correlation analysis, and multiple regression analysis were employed, thus facilitating a robust process of inference. In this investigative journey, the nuances of product features, societal influences, and brand perception stood as independent variables, critically analyzed for their bearing on smartphone purchasing decisions. Correlation studies manifested a strong linkage between the dependent variable - the consumer’s buying decision, and all the outlined independent variables. Furthermore, the regression analysis highlighted the profound influence of brand perception, product attributes, and societal factors on the consumer buying trajectory. This study not only paves the way for insightful managerial and academic discourse but also stands as a beacon for scholars seeking theoretical directions in this domain. Moreover, the findings encapsulated in this study could forge a path for the creation of adept marketing stratagems in the realm of smartphones.